Neuroeducation: understanding neural dynamics in learning and teaching - Pradeep, K.; Sulur Anbalagan, Rajalakshmi; Thangavelu, Asha Priya; Aswathy, S.; Jisha, V. G.; Vaisakhi, V. S. (Frontiers in Education, 2024)
Neuroeducation, an emerging interdisciplinary field at the intersection of neuroscience and education, investigates into the complex processes underpinning learning which offering novel insights and methodologies. This article examines the foundational principles of neuroeducation, descriptive dynamic interplay between neuronal mechanisms and pedagogical strategies. Central to this exploration is an appreciation for the brain's remarkable plasticity and adaptability, highlighting how learning experiences sculpt neuronal networks. Utilizing advanced imaging techniques and rigorous neuroscientific research, a wealth of insights has emerged, enhancing our understanding of cognition, memory formation, and information processing. These insights enrich our comprehension of individual learning mechanisms and guide the development of effective educational interventions. Grounded in interdisciplinary collaboration, neuroeducation seamlessly integrates perspectives from neuroscience, psychology, and education to develop instructional approaches aligned with the brain's intrinsic learning processes. This collaboration nurtures, innovation in teaching methodologies, enhances student engagement, and bolsters academic achievement. Furthermore, the integration of technology into educational practices, ranging from brain-computer interfaces to immersive virtual reality experiences, presents new possibilities for enhancing learning engagements and accommodating diverse learning styles and curricula. Through the strategic use of technology's transformative power, educators can create immersive learning environments that stimulate cognitive processes and enhance knowledge retention. Neuroeducation emerges as a transformative force in educational theory and practice, empowering educators to design pedagogical approaches finely attuned to the complexities of the human brain, this paves the way for a more inclusive and effective educational landscape. This study is nested within a systematic review of the past 15 years of digital depository research and models of neuroeducational discourses, underscoring the field's evolving nature and its impact on contemporary education.